The protective effects of garlic (Allium sativum var. Solo Garlic) extract mitigates piroxicam-induced liver damage and oxidative stress in rats - Maya Nurwartanti Yunita; Hani Plumeriastuti; Bodhi Agustono; Moch. Ilham Riza Fahlefi; Aprilia Rizki Fadilla; Ragil Ayu Pangastutie; Shelly Oktania Nurvita Sari; Muhammad Fikri Syamsuri; Muhammad Alivio Putra Fajar; Reina Puspita Rahmaniar; Md. Aliar Rahman (Open Veterinary Journal)
Background: Piroxicam, a nonsteroidal antiinflammatory drug, is commonly used to induce inflammation in experimental models of inflammatory bowel disease (IBD). Piroxicam can modulate the immune system and disrupt the mucosal barrier, leading to increased production of reactive oxygen species.